Advanced Oxidation Processes Using Zinc Oxide Nanocatalyst for Detoxification of Some Highly Toxic Insecticides in an Aquatic System Combined With Improving Water Quality Parameters - Massoud, Ahmed; El-Mehasseb, Ibrahim; Saad Allah, Moustafa; Elmahallawy, Ehab Kotb; Alsharif, Khalaf F.; S. Ahmed, Mohamed; Derbalah, Aly Soliman (Frontiers in Environmental Science, 2022)
Pesticides are among the major organic pollutants, and their random extensive applications threaten human health and ecosystems. Clearly, detoxification of toxic insecticides from the aquatic system remains a global priority. In the present study, a zinc oxide nanocatalyst was synthesized with suitable properties to achieve complete degradation of some insecticides (dimethoate and methomyl) from aqueous media. The ZnO catalyst was used in normal and in nano-size as a part of an advanced oxidation process in the presence of H2O2 and UV rays. The complete detoxification of the tested pesticides after treatment with the most effective process (ZnO(s)/H2O2/UV) was then examined by exploring the biochemical and histopathological changes in the liver and kidneys of treated rats compared to the control. The effect of water treatment by ZnO (nano)/H2O2/UV on the water quality parameters of treated water was also investigated. Interestingly, the present study reported that the degradation rates of the investigated insecticides were faster using the nano-sized ZnO catalyst than the regular ZnO catalyst. In this respect, complete decomposition of the tested insecticides (100%) under the ZnO(s)/H2O2/UV system was achieved after 320 min of irradiation. The half-lives of the tested insecticides under ZnO(c)/H2O2/UV were 43.86 and 36.28 for dimethoate and methomyl, respectively, while under the ZnO(c)/H2O2/UV system, the half-live values were 27.72 and 19.52 min for dimethoate and methomyl, respectively. On the other hand, there were no significant changes in the biochemical and histological parameters of rats treated with remediated water when compared to the control group. The treatment of water by zinc oxide nanocatalyst improved the quality of water parameters. Collectively, advanced oxidation processes using ZnO nanocatalyst can be considered as a promising treatment technology for the complete detoxification of methomyl and dimethoate in water. However, further research is warranted for the identification of the potential breakdown products.